Pengaruh Risiko Pembiayaan Terhadap Kinerja Keuangan Bank Umum Syariah di Indonesia - Firdausy, Ranti Putri; Satria, Doni (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study offers significant new insights into the relationship between financing risk, as determined by Non-Performing Financing (NPF), and Islamic Commercial Banks' financial performance, as determined by Return On Asset (ROA). In this study, data from 10 Islamic Commercial Banks in Indonesia between 2016 and 2023 are analyzed using panel data regression. The results show that NPF significantly lowers ROA. This suggests that inadequate financing risk management can have a significant negative influence on the profitability of Islamic banks, as the greater the NPF level, the worse the bank's financial performance. The aforementioned discovery underscores the need of executing efficient risk mitigation strategies to guarantee the steadiness and durability of banks' fiscal outcomes. It also emphasizes how Islamic banks must concentrate more on reducing financing risk if they want to increase market share and perform better.